Weather on Independence Day at the important cities of India (MAUSAM, 1959)
Independence Day, 15 August 1947, is a land mark in the history of India. It is only natural that the people of India should re-joice and celebrate with enthusiasm each year the anniversary of this historic day. 15 August falls during the peak period of the southwest monsoon, a season of rain and cloudy skies. The organisers and participants in the celebrations, which are held even in the smallest village, have one question uppermost in their mind. What is the weather going to be and will it rain? It is the purpose of this note to present an analysis, from past records, of the weather on this day at the important cities of India. It is expected that from the analysis of the data it will be possible to obtain a fair idea of the probability of rain and cloudiness on Independence Day.